Nanosatellite X-ray lobster eye optics – measurement of optical performance - Vladimír Tichý; Šárka Němcová; René Hudec; Martin Míka (Acta Polytechnica)
This paper presents the results of tests of a one-dimensional Schmidt lobster-eye prototype module. The optics benefits from the new technology used for the mechanical part which ensures accurate positioning of individual mirrors, resulting in a sharp image in the focal plane. The prototype is designed for X-ray energy of around 1 keV, but it was tested in the visible part of the spectrum. FWHM is determined. The experimental results agree well with the simulations